(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article presents a comparative analysis of satirical elements in Oscar Wilde’s The Picture of Dorian Gray and the works of Uzbek satirical prose, particularly focusing on Abdulla Qahhor’s writings. While Wilde’s novel is traditionally examined through the lens of aestheticism and decadence, it contains significant satirical components targeting Victorian hypocrisy, aristocratic vanity, and the moral contradictions of a society obsessed with appearance. Parallels are drawn with Uzbek satirical tradition, where writers like Abdulla Qahhor similarly employed irony, allegory, and grotesque to critique social injustices, bureaucratic absurdity, and moral decay under the constraints of censorship. The study examines how both traditions use satire as a vehicle for social criticism while adapting their techniques to specific cultural and political contexts. Special attention is paid to typological similarities in artistic devices-paradox, irony, symbolism, and the mask motif-as well as divergent approaches shaped by distinct historical circumstances. The findings reveal that despite differences in cultural frameworks, both Wilde and Uzbek satirists deploy satire to expose the gap between appearance and reality, challenging readers to recognize uncomfortable truths about their societies.